Penile Cancer Diagnosis and Treatment - Spiess, Philippe E.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Penile Cancer: Diagnosis and Management provides a comprehensive overview of penile cancer for medical and surgical urologists oncologists, and other healthcare professionals. This book highlights many of the significant advances made in this field, which include a discussion of penile-sparing surgical and radiotherapeutic approaches to select primary penile tumors typically of lower stage and grade as well as advances in our understanding of the epidemiology, risk factors, and pathophysiology of penile cancer. The book also addresses many of the novel diagnostic and therapeutic surgical approaches to inguinal lymph nodes, including dynamic sentinel node biopsy and minimally invasive surgery. The authors also discuss many of the clinical pearls and surgical considerations that can optimize treatment outcomes while minimizing the morbidity and inherent risk of complications in patients undergoing an open inguinal lymph node dissection. Lastly, the volume presents a discussion of the paradigm shift in the management of bulky inguinal lymph node metastases from penile cancer consisting of neoadjuvant systemic chemotherapy followed by consolidative surgical resection, which can offer an improved likelihood of survival as shown in a recent phase 3 clinical trial.      Penile Cancer: Diagnosis and Management will serve as a resource for clinicians and researchers seeking an overview on the current state of knowledge in penile cancer. The editor has gathered leading worldwide experts in this field who have written a very practical and useful textbook for clinicians in an attempt to optimize patient outcomes and promote the pivotal scientific advances made in recent years.
1. Epidemiology and Risk Factors for Penile Cancer -- 2. Staging and Risk Stratification in Penile Cancer -- 3. Pathology of Penile Cancer and Its Precursor Lesions -- 4. Evolving Imaging Modalities in the Diagnosis and Staging of Penile Cancer -- 5. Penile-Sparing Approaches to Primary Penile Tumors -- 6. Surgical Concepts and Considerations of Inguinal Lymph Node Dissection for Penile Cancer -- 7. Minimally Invasive Surgical Approaches to Penile Cancer -- 8. Applications of Radiation Therapy in the Management of Penile Cancer -- 9. Multimodal Approach to the Management of Locally Advanced and Metastatic Penile Cancer -- 10. New Horizons in the Diagnosis, Treatment, and Prevention of Penile Cancer.
Keywords: Urology; Oncology .; Surgical oncology; Urology; Oncology; Surgical Oncology